Developing a Healthcare and Medical School at King Faisal University: Implications for Educational Performance and Cost-Effectiveness - Ali Almomin; Abu Elnasr E. Sobaih (European Journal of Investigation in Health, Psychology and Education, 2023)
This research explored the potential of developing a university healthcare and medical school within King Faisal University, Saudi Arabia, by merging four medical and/or healthcare colleges within the institution into a medical school. The objective of a medical school is to produce professionals who are capable of performing the most fundamental tasks in healthcare and medicine up to the expectations of the market. This research explored various case studies involving mergers, their importance, and how they were conducted to inform this research study. This study adopted a qualitative research approach to collect data from healthcare and medical colleges’ senior management, including deans, vice-deans, as well as heads of departments. The results showed several benefits of mergers, although some challenges were also raised. Culture, which some interviewees identified as change-resistant and risk-averse, was recognised as a key challenge for implementing mergers. Additionally, the need for generating funds for the merger projects was identified as a challenge at the start of the initiatives. Furthermore, compliance with regulations and laws at a public university is another challenge. This study identified the need for a strategic framework that builds on stakeholders’ involvement and proper communication and addresses the proposals’ repercussions. Some implications for educational performance and cost effectiveness were highlighted.